THE SIGNIFICANCE OF MIRZO ULUGBEK’S HISTORY OF FOUR ULUSES IN YOUTH EDUCATION - Turdiyev Bahritdin Samiyevich (Galaxy International Interdisciplinary Research Journal, 2021)
The article provides a scientific analysis of the role of the work of Mirzo Ulugbek "The History of Four Nations" in the education of young people.